Radiological characteristics of neuromyelitis optica spectrum disorder in Egypt. Issue 3 (24th February 2022) - Nasreldein, Ahmed; Farweez, Hasan; Abo Elfetoh, Noha; Badawy, Eman R.; Mahmoud, Doaa M.; Hassanein, Sara; Khedr, Eman
Abstract: Background: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune demyelinating disease of the central nervous system, which mainly affects the optic nerves and the spinal cord. Magnetic resonance imaging (MRI) plays an important role in the diagnosis of NMOSD based on the 2015 consensus criteria. Methods: The objective of this study was to describe the MRI characteristics of NMOSD patients in Egypt. This were a prospective, observational study on patients fulfilling the 2015 diagnostic criteria of NMOSD. Patients were recruited consecutively from the Neurology, Psychiatry and Neurosurgery hospital, Assiut University Hospitals, Egypt from March 2019 until August 2020. Data on demographics, clinical and laboratory features were collected. MRI scan results were reviewed for each patient and compared according to Aquaporin4‐seropositivity. Results: Ninety patients fulfilled NMOSD diagnostic criteria. The mean age at onset was 30.7±11.8 with a female predominance of 3:1. AQP4 antibodies were positive in 77/90 patients (85.6%). Seventy‐two patients (80%) had acute myelitis, 44 cases (61.1%) had longitudinally extensive transverse myelitis (LETM) and 61 cases (87.1%) had a central position in the cord. Bright spotty lesions (BSL) were found in 44 cases (61.1%). The most common site of cord involvement was the cervical region. Abnormal MRI brain scans were found in 81.1% of patients. No statistically significant differences could be found between the two groups. Conclusion: There was a high frequency of abnormal spine and brain MRI findings in the Egyptian population. Even though no specific patterns were typical for AQP4‐specific serostatus, certain findings may suggest NMOSD diagnosis and warrant AQP4‐IgGs testing. Abstract : Magnetic resonance imaging (MRI) plays an important role in the diagnosis of NMOSD based on the 2015 consensus criteria and its differentiation from other mimickers. High frequency of abnormal Spine and Brain MRI findings was found in Egyptian population. Even though no specific patterns were typical for AQP4‐seropositive patients, certain findings may suggest NMOSD diagnosis and warrant AQP4‐IgGs testing.